Potency of six isolates of biocontrol agents endophytic Trichoderma against fusarium wilt on banana - J Taribuka; A Wibowo; S M Widyastuti; C Sumardiyono (Journal of Degraded and Mining Lands Management, 2017)
Fusarium wilt caused by F. oxysporum f.sp. cubense is one of very damaging banana plant diseases which can cause plant death. Disease control using intensive chemical fungicides will have negative impacts on the environment and humans. Endophytic Trichoderma is one of the biological control agents which can reduce the amount of inoculum of pathogens, so it can reduce disease intensity. The objectives of this study was to assess the ability of endophytic Trichoderma in inducing plant resistance against fusarium wilt. Endophytic Trichoderma was obtained from healthy roots of banana from three regencies in Yogyakarta, namely Trichoderma harzianum.swn-1, T. harzianum.swn-2, T. harzianum.psr-1, T. asperrellum, T. gamsii, and T. koningiopsis. Research on induced resintance was conducted in the greenhouse with polybag using Completely Randomized Design with 14 treatments and 3 replications. The results showed that the ability of Trichoderma gamsii antagonism against F. oxysporum f.sp. cubense was 60.61%. T. asperellum and T. harzianum.swn-2 could suppress this disease resulted in disease intensity of 8.33% which categorize as resistant. Trichoderma harzianum.psr-1 was significantly different in stimulating plant vegetative growth. Induced resistance by using endophytic Trichoderma spp. against  F. oxysporum f.sp. cubense showed increase in total phenolic compounds on the third and fourth weeks as well as peroxidase activity on the third, fourth and fifth weeks.  Observation of lignification on  the fifth week  showed that lignification occurred in root xylem